2013
DOI: 10.1160/th12-10-0758
|View full text |Cite
|
Sign up to set email alerts
|

High on-treatment platelet reactivity – definition and measurement

Abstract: SummaryIn the last decade, several studies revealed inter-patient response variability to antiplatelet agents: patients who display negligible or no responses to these drugs are considered poor responders, or “resistant” to treatment. In order to identify poor responders to an antiplatelet drug, laboratory tests of platelet function that specifically explore the platelet activation pathway that is targeted by the drug should be utilised. In addition, they should be performed both at baseline and during treatme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(29 citation statements)
references
References 77 publications
0
26
0
2
Order By: Relevance
“…Data showed that plasma concentrations of MMP-2, MMP-9, and TIMP-4 were similar both in HPR patients and their counterparts (Figure 1). Since concordance among different tests in the identification of patients with HPR is limited [35], we have compared the concentrations of matrix metalloproteinases and their inhibitor in HPR patients classified by different methods. Despite testing different criteria for aspirin-HPR (cut off point >15%, >20%, >30 AU, >3.1 ng/ml, and >5.8 ng/ml, as appropriate), we did not show a significant difference in MMP-2, MMP-9, and TIMP-4 concentrations in plasma of aspirin responding and aspirin-HPR patients (Table 2).…”
Section: Resultsmentioning
confidence: 99%
“…Data showed that plasma concentrations of MMP-2, MMP-9, and TIMP-4 were similar both in HPR patients and their counterparts (Figure 1). Since concordance among different tests in the identification of patients with HPR is limited [35], we have compared the concentrations of matrix metalloproteinases and their inhibitor in HPR patients classified by different methods. Despite testing different criteria for aspirin-HPR (cut off point >15%, >20%, >30 AU, >3.1 ng/ml, and >5.8 ng/ml, as appropriate), we did not show a significant difference in MMP-2, MMP-9, and TIMP-4 concentrations in plasma of aspirin responding and aspirin-HPR patients (Table 2).…”
Section: Resultsmentioning
confidence: 99%
“…Multiple methods (e.g., VASP, impedance aggregometry, light transmission aggregometry, PFA-100 ® system, flow cytometry, etc.) are used to measure the level of platelet reactivity during antiplatelet treatment [17]. Accordingly, several criteria have been proposed by expert working groups to define high on-treatment platelet reactivity in the setting of PCI.…”
Section: Discussionmentioning
confidence: 99%
“…Methods for the determination of antiplatelet therapy efficacy currently have low specificities and sensitivities (7,15). The issue of resistance to antiplatelet therapy has raised many questions in the area of neurovascular diseases (26)(27)(28).…”
Section: Discussionmentioning
confidence: 99%